Which Direction Should the Future of Timorese Education Take? - Pascoal Soares Madeira; Virgindo Andrade Fátima (Mandalika Journal of Business and Management Studies, 2026)
This study examines the future direction of Timorese education by exploring educational pathways capable of addressing contemporary and future challenges. The research employed a descriptive qualitative approach based on observations, conversations, semi-structured interviews with Timorese academics, teachers, and students, as well as documentary analysis of educational policies, including the Basic Education Law No. 14/2008 and its 2026 revision. The findings indicate that the future of Timorese education should be grounded in the principles of Timorization, which emphasize the integration of local culture, language, historical experience, and national identity into educational practices. The study highlights the relevance of Pedagogia do Maubere as a contextual educational framework that enables students to become active interpreters of their own realities while strengthening educational sovereignty and social responsibility. Furthermore, the findings reveal the importance of balancing academic competence with ethical values through the dual principle of “Science and Attitude.” Participants also identified challenges related to teacher professionalism, reading practices, educational infrastructure, and the implementation of culturally relevant curricula. This study contributes to the ongoing discussion on educational reform in Timor-Leste by integrating Timorization, educational ethics, Pedagogia do Maubere, and professional responsibility within a single analytical framework. The findings suggest that culturally grounded educational policies and continuous investment in human resources are essential for promoting educational quality, equity, and national development.